Cancer Risk Awareness and Concern among Women with a Family History of Breast or Ovarian Cancer. Issue 1 (2nd January 2016) - Andersen, M. Robyn; Thorpe, Jason; Buist, Diana S. M.; Beatty, J. David; Watabayashi, Kate; Hanson, Nancy; Resta, Robert; Chubak, Jessica; Urban, Nicole
Abstract : Women with a documented deleterious mutation in BRCA1 or BRCA2 are at substantially elevated risk for ovarian cancer. To understand what percentage of women with high-risk family histories know their risk is elevated we surveyed 1, 885 women with a high- or moderate-risk family history and no personal history of breast or ovarian cancer, and asked about their perceived risk of breast and ovarian cancer. Among high-risk women, fewer than 20% reported use of genetic counseling, and knowledge of elevated risk of ovarian cancer was low. Prior genetic counseling was associated with greater perceived risk for ovarian cancer. Results suggest that most high-risk women (>75%) do not know their risk for ovarian cancer. Identification of potentially high-risk women for referral to genetic counseling may improve informed ovarian cancer risk management.